2016
DOI: 10.1002/jcla.22079
|View full text |Cite
|
Sign up to set email alerts
|

Serum endocan levels in endometrial and ovarian cancers

Abstract: Although benign ovarian or endometrial disorders do not lead to expression of endocan, malignant cases can result in measurable endocan levels. This may be useful in differentiating benign and malign diseases of the endometrium or ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…An increase in tissue or blood endocan level shows endothelial activation and neovascularization, which are indicators of inflammation and tumor progression [18]. Therefore, blood endocan level has been used as a biomarker for various cancers including ovarian or endometrial carcinoma, pre-eclampsia, and inflammation-related diseases such as cirrhosis, sepsis, hypertension, and Behcet's disease [18][19][20][21][22][23][24]. As well as presence and severity of inflammation-related diseases, these markers indicate cardiovascular and metabolic risk of patients [25].…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…An increase in tissue or blood endocan level shows endothelial activation and neovascularization, which are indicators of inflammation and tumor progression [18]. Therefore, blood endocan level has been used as a biomarker for various cancers including ovarian or endometrial carcinoma, pre-eclampsia, and inflammation-related diseases such as cirrhosis, sepsis, hypertension, and Behcet's disease [18][19][20][21][22][23][24]. As well as presence and severity of inflammation-related diseases, these markers indicate cardiovascular and metabolic risk of patients [25].…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…Thus, ESM-1 plays a role in angiogenesis and inflammation. Numerous studies have demonstrated that ESM-1 can be used as a potential biomarker for detection in gastric cancer 36 , bladder cancer 37 , colorectal cancer 28 , hepatocellular carcinoma 38 , pituitary adenoma 39 , ovarian cancer 40 , breast cancer 41 , and acute leukemia 20 , but ESM-1 has not been investigated in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, endocan levels in PCOS, as in other chronic diseases, were found to be higher than healthy control groups. 1,13,16,[18][19][20] Th e aim of this study is to compare the endocan level in PCOS patients with the healthy control group and to show the relationship between some cardiovascular risk indicators accompanying PCOS and endocan level.…”
Section: Introductionmentioning
confidence: 99%